High discontinuation rate of azathioprine in autoimmune hepatitis, independent of time of treatment initiation. (11th June 2020) - Pape, Simon; Gevers, Tom J. G.; Vrolijk, Jan Maarten; van Hoek, Bart; Bouma, Gerd; van Nieuwkerk, Carin M. J.; Taubert, Richard; Jaeckel, Elmar; Manns, Michael P.; Papp, Maria; Sipeki, Nora; Stickel, Felix; et al.
Abstract: Background: Guidelines regarding treatment for autoimmune hepatitis (AIH) favour two strategies for azathioprine (AZA) introduction: concurrent with steroids at induction or delayed by 2‐4 weeks. The safety and efficacy of both strategies have been unexplored. Methods: We established a cohort of 900 AIH patients from 12 centres in 7 European countries. There were 631 patients who used AZA as part of the therapeutic regimen. We distinguished two groups: patients with early AZA (<2 weeks) or delayed AZA initiation (≥2 weeks). Primary outcome was discontinuation of AZA in the first year of treatment. Cox regression and propensity score matching was performed to determine difference in outcomes between groups. Results: Patients with early AZA initiation had significantly lower transaminases and bilirubin at baseline. Discontinuation rates of AZA did not differ between early and delayed starters (16.6% vs 14.2%), which did not reach statistical significance (hazard ratio 0.97, 95% confidence interval 0.61‐1.55, P  = .90). Stratification according to baseline disease activity or propensity score matching did not alter the results. Main reason for AZA discontinuation was intolerance to treatment (14.0% vs 13.2%, P  = .78) with nausea and vomiting as main side effects. AIH remission rates were comparable among groups. Conclusion: The discontinuation rate of AZA in AIH treatment is ~15% in the first year of treatment. Early or delayed AZA initiation does not differ in remission and discontinuation rates in AIH induction therapy. Our data suggest that either strategy may be used as part of AIH treatment.